How does the public understand the causes of mental disorders? An analysis of Irish news media before and during the COVID-19 pandemic. - Leigh Huggard; Cliódhna O'Connor (PLoS ONE, 2023)
Public perceptions of the determinants of mental illness have important implications for attitudes and stigma, but minimal previous research has explored how causal attributions are spontaneously invoked in everyday public discourse. This study investigated how causal explanations for mental illness are disseminated in popular Irish news media, in the two years before and after the onset of the COVID-19 pandemic. Keyword searches of a news media database identified 1,892 articles published between March 2018 to March 2022 that mentioned one of six categories of mental disorders: anxiety disorders, mood disorders, substance-related disorders, personality disorders, eating disorders, and psychotic disorders. Overall, 25% of the identified articles contained a causal explanation for mental illness. Inductive content analysis revealed the content and prevalence of eight types of causal explanations for mental disorders. Overall, attributions to life events/experiences, the cultural/societal environment, interpersonal relations, and health and lifestyle factors occurred more frequently than attributions to biological or psychological determinants. Life events/experiences were the most common explanation for anxiety and personality disorders, cultural/societal environment for eating disorders, and health/lifestyle factors for mood and psychotic disorders. Interpersonal factors in mental illness aetiology became more salient following the COVID-19 pandemic. The findings emphasise the need for theory and research on lay explanations of mental disorders to account for diversity, both in the range of attributions invoked, and in how attributional patterns shift across time and mental disorders category.